Enhancing Engineering Electromagnetics Education: A Comparative Analysis of Synchronous and Asynchronous Learning Environments - Bilad, Muhammad Roil (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
This study evaluates implementation of asynchronous learning in teaching engineering electromagnetics module. A group of first-year engineering students participated in the study. The instruction was divided into two periods, with the first period using asynchronous online mode and the second period using synchronous face-to-face mode. The performance evaluation was based on essay questions on class tests, and the data variances were statistically analysed. In addition, student feedback was gathered through interviews conducted at the end of the semester. In terms of overall performance, the results indicate that synchronous and asynchronous learning methods were equally effective, as no significant difference was found. However, individual student grades revealed a variety of outcomes for the asynchronous learning method, suggesting that students have different learning preferences and levels of adaptability. Positive feedback for asynchronous learning included the ability to adjust the pace of learning and conveniently access course materials. Students valued the availability of recorded lectures for reviewing difficult subject matter. Students with lower study motivation or limited experience with independent learning were negatively affected by the absence of scaffolding and immediate feedback in the asynchronous learning approach. Some students emphasized the importance of face-to-face interaction with the instructor, especially in a subject like electromagnetics that requires intuitive thought and elaboration.